An epidemiological investigation of training and injury patterns in triathletes - Zwingenberger, S.; Valladares, R. D.; Walther, A.; Beck, H.; Stiehler, M.; Kirschner, S.; Engelhardt, M.; Kasten, P. (Journal of Sports Sciences, 2014)
Associated with the trend towards increased health consciousness and fitness, triathlon has established itself as a sport for masses. The goals of this study were to evaluate injury risk factors of non-professional triathletes and to compare prospective and retrospective evaluation methods. Using an online survey, 212 triathletes retrospectively answered a questionnaire about their training habits and injuries during the past 12 months. Forty-nine of these triathletes participated in a 12-month prospective trial. Injuries were classified with regard to the anatomical location, type of injury, incidence and associated risk factors. Most injuries occurred during running (50%) followed by cycling (43%) and swimming (7%). Fifty-four per cent (retrospective) and 22% (prospective) of the injuries were contusions and abrasions, 38% (retrospective) and 46% (prospective) were ligament and capsular injuries, 7% (retrospective) and 32% (prospective) were muscle and tendon injuries and 1% (retrospective) and 0% (prospective) were fractures. The incidence of an injury per 1000 training hours was 0.69 (retrospective) and 1.39 (prospective) during training and 9.24 (retrospective) and 18.45 (prospective) during competition. The main risk factor for injury in non-professional triathlon is participation in a competitive triathlon event. A retrospective design may underestimate the rate of overuse injuries.